Immediate and Long term Complication associated with Non-Conventional ECT in Tertiary care Hospital Faisalabad - Siddique, Irum; Iijaz, Sadaf; Ikram, Tayyaba (Journal of Pakistan Psychiatric Society, 2020)
Immediate and Long term Complication associated with Non-Conventional ECT in Tertiary care Hospital Faisalabad.